2005
DOI: 10.1002/smll.200500169
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability and Lasing of CdS Nanowires Coated by Amorphous Silica

Abstract: Coaxial nanowires: Single‐crystalline CdS nanowires (NWs) are successfully coated with a uniform silica layer to give coaxial structures (see TEM image). The coating improves the high‐temperature stability of the NWs and enhances their photoluminescence emission, compared with uncoated NWs. Stimulated emission and lasing occur under high‐intensity optical excitation. The surface‐modified CdS NWs have potential applications in photonic and optoelectronic fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…12),13) After being coated by a film of loose silica, the thermal stability of a single-crystalline CdS nanowire has been improved up to around 750°C. 16) By comparing the data in literature with the results of XRD and DSC-TG in the present research, we can conclud that the thermal stability of CdS particles has been further enhanced to more than 900°C by the hydrothermally densified SiO2-CeO2 matrix.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…12),13) After being coated by a film of loose silica, the thermal stability of a single-crystalline CdS nanowire has been improved up to around 750°C. 16) By comparing the data in literature with the results of XRD and DSC-TG in the present research, we can conclud that the thermal stability of CdS particles has been further enhanced to more than 900°C by the hydrothermally densified SiO2-CeO2 matrix.…”
Section: Resultssupporting
confidence: 70%
“…4),12),13) Former researches showed that silica deposition on the surface of CdS quantum dots could improve its stability against photochemical degradation; 14),15) the thermal stability of CdS nanowires were enhanced by a coating of amorphous silica, 16) and it could be further increased to ~1200°C after been occluded in a densified zircon. 17) As shown in literature, a densified coating is preferred to enhance the oxidation resistance, which is generally sintered with the protection of N2 or Ar atmosphere.…”
Section: )8)mentioning
confidence: 99%
“…Finally, for hybrid systems, there are two reports on nanocables of CdSe and CdS coated with dielectric materials such as SiO 2 [76,118]. The CdSe and CdS nanowires were coated with amorphous silica to prevent surface-state recombination and to protect the surface from oxidation and degradation.…”
Section: (B) Hybrid Systems and Heterostructuresmentioning
confidence: 99%
“…On the other hand, silicon dioxide (SiO 2 ) is known as one of the most suitable insulating material for nanowire passivation owing to its excellent insulating property, low dielectric constant, and high mechanical strength as well as compatibility with other materials widely used in integrated circuits (IC) fabrication. SiO 2 is also optically transparent for light absorption or emission of semiconductor nanowires, resulting in minimal destruction of their intrinsic optical properties such as photoluminescence [26,27]. In this paper, we report the fabrication of ZnS-core/SiO 2 -shell nanowires by using a two-step process: the thermal evaporation of ZnS powders and the sputter-deposition of SiO 2 .…”
Section: Introductionmentioning
confidence: 98%